Requirements for Heterologous Production of a Complex Metalloenzyme: the Membrane-Bound [NiFe] Hydrogenase - Lenz, Oliver (American Society for Microbiology, 2005)
By taking advantage of the tightly clustered genes for the membrane-bound [NiFe] hydrogenase of Ralstonia eutropha H16, broad-host-range recombinant plasmids were constructed carrying the entire membrane-bound hydrogenase (MBH) operon encompassing 21 genes. We demonstrate that the complex MBH biosynthetic apparatus is actively produced in hydrogenase-free hosts yielding fully assembled and functional MBH protein.